(untitled) (ETIMA, 2025)
A scanning electron microscope (SEM) is a type of electron microscope that produces images of a sample by scanning its surface with a focused beam of electrons. The electrons interact with the atoms in the sample, generating various signals that contain information about the surface topography and composition of the sample. The electron beam is scanned in a raster pattern, and the beam position is combined with the intensity of the detected signal to create an image. In the most common SEM mode, secondary electrons emitted by atoms excited by the electron beam are detected using a secondary electron detector (Everhart-Thornley detector). The number of secondary electrons that can be detected, and thus the signal intensity, depends, among other factors, on the sample’s topography. Some SEMs can achieve resolutions better than 1 nanometer. Samples are observed under high vacuum in a conventional SEM or under low vacuum or wet conditions in a variable pressure or environmental SEM. They can also be examined across a wide range of cryogenic or elevated temperatures using specialized instruments. The instrument model is Tescan Vega 3 LMU. In dentistry, samples must first be prepared using an appropriate method depending on what will be analyzed. After that, they need to be further prepared for microscopy. In this case, the sample was applied only to a holder with a double-sided adhesive carbon tape without coating. The analyses were performed under high vacuum using an SE detector for morphological examination and an EDS detector for point chemical analysis. For handling the implants, sterile gloves were used to prevent additional contamination.